The Influence of Reward and Leadership Style on Employee Performance With Work Motivation as an Intervening Variable at The Sumbar Bapenda Office - wijayanti, emillia; wijayanti, Marta Widian Sari; Silvia Sari (Profesional Muda Cendekia Publishing, 2025)
This study aims to determine the effect of rewards and leadership style on employee performance through work motivation as an intervening variable at the West Sumatra BAPENDA Office. The method of data collection through surveys and distributing questionnaires to employees as respondents with a sample size of 56 respondents using a quantitative approach. The data analysis technique used is Structural Equation Modeling (SEM) Analysis with Partial Least Square (PLS) 3.0. The results of the study indicate that there is a significant positive effect between Leadership Style on Employee Performance at the West Sumatra Provincial Revenue Agency Office. There is a positive and significant effect between Leadership Style on Work Motivation at the West Sumatra Provincial Revenue Agency Office. There is a positive and insignificant effect between Work Motivation on Employee Performance at the West Sumatra Provincial Revenue Agency Office. There is a positive and insignificant effect between Reward on Employee Performance at the West Sumatra Provincial Revenue Agency Office. There is a positive and insignificant effect between Reward on Work Motivation at the West Sumatra Provincial Revenue Agency Office. Leadership Style has a positive and significant effect on Employee Performance through Work Motivation at the West Sumatra Provincial Revenue Agency Office. 7. Rewards have a positive and insignificant effect on Employee Performance through Work Motivation at the Regional Revenue Agency Office of West Sumatra Province. Keywords: Reward, Leadership Style, Employee Performance, Work Motivation